Direct Targeting of CREB1 with Imperatorin Inhibits TGFβ2‐ERK Signaling to Suppress Esophageal Cancer Metastasis. Issue 16 (1st July 2020) - Xu, Wen Wen; Huang, Zhi‐Hao; Liao, Long; Zhang, Qi‐Hua; Li, Jun‐Qi; Zheng, Can‐Can; He, Yan; Luo, Ting‐Ting; Wang, Yang; Hu, Hui‐Fang; Zuo, Qian; Chen, Wen‐You; et al.
Abstract: Metastasis accounts for 90% of cancer death worldwide, and effective therapeutic strategies are lacking. The aim of this work is to identify the key drivers in tumor metastasis and screen therapeutics for treatment of esophageal squamous cell carcinoma (ESCC). Gene Ontology analysis of The Cancer Genome Atlas (TCGA) gene expression datasets of ESCC patients with or without lympy metastasis identifies that TGF β 2 is highly enriched in the pathways essential for tumor metastasis and upregulates in the metastatic ESCC tumors. High TGF β 2 expression in ESCC correlates with metastasis and patient survival, and functionally contributes to tumor metastasis via activating extracellular signal‐regulated kinases (ERK) signaling. By screening of a library consisting of 429 bioactive compounds, imperatorin is verified as a novel TGF β 2 inhibitor, with robustly suppressive effect on tumor metastasis in multiple mice models. Mechanistically, direct binding of imperatorin and CREB1 inhibits phosphorylation, nuclear translocation of CREB1, and its interaction with TGF β 2 promoter, represses TGF β 2 expression and fibroblasts‐secreted CCL2, and then inactivates ERK signaling to block cancer invasion and abrogates the paracrine effects of fibroblasts on tumor angiogenesis and metastasis. Overall, the findings suggest the use of TGF β 2 as a diagnostic and prognostic biomarker and therapeutic target in ESCC, and supports the potential of imperatorin as a novel therapeutic strategy for cancer metastasis. Abstract : This work suggests the clinical and functional role of TGF β 2 in esophageal cancer metastasis. Imperatorin is verified with a robustly suppressive effect on tumor invasion and metastasis in vitro and in vivo. Mechanistically, imperatorin can directly bind with CREB1 and inhibits its phosphorylation and interaction with TGF β 2 promoter, then inactivates extracellular signal‐regulated kinases (ERK) signaling and fibroblasts‐secreted CCL2 to block tumor angiogenesis and metastasis.